Retraction: Development and validation of a brief form of the nursing questionnaire on organizational health - Vitale, Elsa; Caputo, Maria; Canonico, Anna (Acta Biomedica Atenei Parmensis, 2021)
ARTICLE RETRACTED AFTER PUBLICATION